Common Identity of Substrate Binding Subunit of Vacuolar H(+)-Translocating Inorganic Pyrophosphatase of Higher Plant Cells - Rea, Philip A. (1992)
There have been conflicting reports in the literature concerning the polypeptide composition of the vacuolar H(+)-translocating inorganic pyrophosphatase (tonoplast H(+)-PPase) of plant cells. The major subunit(s) of the enzyme have been attributed to polypeptides of relative molecular weight (M(r)) 64,500 (Beta vulgaris), 67,000 (Beta vulgaris), 73,000 (Vigna radiata), and 37,000 to 45,000 (Zea mays). Here, we reconcile these differences to show, through the combined application of independent purification, affinity-labeling, sequencing, and immunological procedures, that the major polypeptide associated with the H(+)-PPase from all of these organisms, and Arabidopsis thaliana, corresponds to the same moiety. The principal polypeptide components of the H(+)-PPase purified from Beta and Vigna by independent procedures have similar apparent subunit masses when subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) under identical conditions (M(r(Beta)) = 64,500; M(r(Vigna)) = 66,000) and exhibit identical kinetics of irreversible inhibition and ligand-modified labeling by [(14)C]-N-ethylmaleimide. Similarly, the M(r) 64,500 and 67,000 polypeptides isolated from Beta by independent methods (cf. C.J. Britten, J.C. Turner, P.A. Rea [1989] FEBS Lett 256: 200-206 versus V. Sarafian and R.J. Poole [1989] Plant Physiol 91: 34-38) are indistinguishable: the two polypeptides comigrate when electrophoresed under the same conditions and yield tryptic fragments with identical overlapping sequences. Because both the N-terminal sequence of the M(r) 66,000 subunit of the H(+)-PPase isolated from Vigna and the direct sequence data from Beta align precisely with the deduced amino acid sequence of cDNAs encoding the H(+)-PPase of Arabidopsis, all three enzymes are inferred to be highly conserved structurally. Accordingly, immunoblots of membranes prepared from Arabidopsis, Beta, Vigna, and Zea, probed with antibody affinity purified against the magnesium inorganic pyrophosphate-binding, M(r) 66,000 polypeptide of Vigna, reveal a single immunoreactive band at M(r) 64,500 to 67,000 in all four preparations. The M(r) 66,000 polypeptide of Zea membranes is, however, prone to proteolysis during membrane fractionation and selective aggregation during sample denaturation for SDS-PAGE. The anomalous M(r) 37,000 to 45,000 subunit pattern previously ascribed to the H(+)-PPase from Zea (A. Chanson and P.E. Pilet [1989] Plant Physiol 90: 934-938) is attributed to loss of the M(r) 66,000 subunit and the appearance of polypeptide fragments of M(r) 44,700 and 39,000 through the combined effects of sample aggregation before SDS-PAGE and proteolysis, respectively. It is, therefore, concluded that the substrate-binding subunit of the tonoplast H(+)-PPase has a common identity in all four organisms.